Self-Acceptance of Parents with Hearing Disability Child - Tiwa, Tellma Monna; Kumaat, Theophany Deasinatalia; Makausi, Alfa Roland (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
Parents sometimes must face the reality that their child is different with other children. One of it is hearing disability. Mostly children with hearing disability also have difficulties in producing sound and even speak. That makes the parents can’t understand their children. This is a qualitative research (case study) that was made to try to understand the struggle of parents who have child with hearing disability. While both of the parents were “normal” how they can accept the condition of their child and also how they see themselves. The result shows that the parents try their best to accept the situation. They even try to give the best therapy and facility that can help their child. All the things that they do is a kind of compensate for their child condition. During their struggle to accept the condition of their child, they also need support from people around them.